Biodistribution of gadolinium-based contrast agents, including gadolinium deposition - Aime, Silvio; Caravan, Peter (Journal of magnetic resonance imaging, 2009)
The biodistribution of approved gadolinium (Gd)‐based contrast agents (GBCAs) is reviewed. After intravenous injection GBCAs distribute in the blood and the extracellular space and transiently through the excretory organs. Preclinical animal studies and the available clinical literature indicate that all these compounds are excreted intact. Elimination tends to be rapid and, for the most part, complete. In renally insufficient patients the plasma elimination half‐life increases substantially from hours to days depending on renal function. In patients with impaired renal function and nephrogenic systemic fibrosis (NSF), the agents gadodiamide, gadoversetamide, and gadopentetate dimeglumine have been shown to result in Gd deposition in the skin and internal organs. In these cases, it is likely that the Gd is no longer present as the GBCA, but this has still not been definitively shown. In preclinical models very small amounts of Gd are retained in the bone and liver, and the amount retained correlates with the kinetic and thermodynamic stability of the GBCA with respect to Gd release in vitro. The pattern of residual Gd deposition in NSF subjects may be different than that observed in preclinical rodent models. GBCAs are designed to be used via intravenous administration. Altering the route of administration and/or the formulation of the GBCA can dramatically alter the biodistribution of the GBCA and can increase the likelihood of Gd deposition. J. Magn. Reson. Imaging 2009;30:1259–1267. © 2009 Wiley‐Liss, Inc.